PERMASALAHAN GURU HONORER TERKAIT KEBIJAKAN PENGHENTIAN REKRUTMEN GURU PNS MENJADI PPPK - Tita Tri Antika Pangestuti; Ratna Wulandari; Enggal miftahul Jannah; Farid Setiawan (Sekolah Tinggi Pariwisata Mataram, 2021)
Teachers are an important role in the world of education, the teaching profession is a noble profession because it is often referred to as heroes without honors. Talking about teachers, there are several statuses ranging from civil servants or PNS of the Ministry of Education and Culture and Ministry of Religion, honorary public school teachers, permanent foundation teachers, nonpermanent foundation teachers, civil servant teachers seconded to private schools, SM3T teachers (scholars educate in frontier, outermost, and disadvantaged areas ), and others. Regarding the many statuses of the teaching profession, it is inseparable from various problems such as the problem of honorary teachers that never ends and with minimal solutions, coupled with the recent policy on stopping the recruitment of PNS teachers in 2021, the purpose of terminating this recruitment is to change the system. recruitment of civil servants to government employees with employment agreements. This policy analysis examines the main points of employment in Law Number 43 of 1999 article 2 paragraph 3 and Law Number 8 of 1974 concerning careers and achievement systems, with this policy it is hoped that the problem of honorary teachers will decrease.